Low‐intensity extracorporeal shockwave therapy ameliorates diabetic underactive bladder in streptozotocin‐induced diabetic rats. (20th April 2018) - Wang, Hsun Shuan; Oh, Byung Seok; Wang, Bohan; Ruan, Yajun; Zhou, Jun; Banie, Lia; Lee, Yung Chin; Tamaddon, Arianna; Zhou, Tie; Wang, Guifang; Lin, Guiting; Lue, Tom F.
Abstract : Objectives: To evaluate the therapeutic effect of once‐weekly low‐intensity extracorporeal shock wave therapy (Li‐ESWT) on underactive bladder (UAB) in the streptozotocin (STZ)‐induced diabetic rat model. Materials and Methods: In all, 36 female Sprague–Dawley rats were divided into three groups: normal control (NC), diabetes mellitus control (DMC), and DM with Li‐ESWT (DM Li‐ESWT). The two DM groups received an intraperitoneal 60 mg/kg STZ injection to induce DM. The Li‐ESWT was applied toward the pelvis of the rats starting 4 weeks after STZ administration and lasting for 4 weeks. The Li‐ESWT was given once weekly, with an energy flux density of 0.02 mJ/mm 2 at 3 Hz for 400 pulses. All rats underwent conscious cystometry, leak‐point pressure (LPP) assessment, ex vivo organ‐bath study, histology, immunofluorescence, and Western Blot analysis. Results: Conscious cystometry revealed voiding dysfunction in the DMC group, whereas the DM Li‐ESWT group showed significantly improved voiding function, reflected in a reduced post‐void residual urine volume and increased LPP compared to the DMC group. Ex vivo organ‐bath studies showed that Li‐ESWT enhanced muscle contractile activity of the bladder and urethra during electrical‐field stimulation and drug stimulation. Histologically, Li‐ESWT significantly restored bladder morphology, reflected by a reduction in the intravesical lumen area and increased muscle proportion of the bladder wall. Western Blot analysis showed higher smooth muscle actin expression in the bladder wall in the DM Li‐ESWT group compared to the DMC group. Immunofluorescence showed decreased nerve‐ending distribution, and destroyed and shortened nerve fibres in the DMC group, and recovery of neuronal integrity and innervation in the DM Li‐ESWT group. Conclusions: In conclusion, Li‐ESWT ameliorated UAB and urinary incontinence in the diabetic UAB rat model. The improvement appears to be the result of restoration of bladder and urethral structure and function by Li‐ESWT. Li‐ESWT is non‐invasive and may become a better alternative therapy for UAB. Further investigations are warranted.